2019
DOI: 10.1038/s41419-019-1481-9
|View full text |Cite
|
Sign up to set email alerts
|

SOX12 promotes colorectal cancer cell proliferation and metastasis by regulating asparagine synthesis

Abstract: The sex-determining region Y (SRY)-box (SOX) family has a crucial role in carcinogenesis and cancer progression. However, the role of SOX12 and the mechanism by which it is dysregulated in colorectal cancer (CRC) remain unclear. Here we analyzed SOX12 expression patterns in two independent CRC cohorts (cohort I, n = 390; cohort II, n = 363) and found that SOX12 was significantly upregulated in CRC, indicating a poor prognosis in CRC patients. Overexpression of SOX12 promoted CRC cell proliferation and metastas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 45 publications
(53 reference statements)
1
55
0
Order By: Relevance
“…Sex determining region Y-box protein (SOX) 12 (SOX12), an important member of the SOX family, was reported to play crucial roles in cardiac, neuronal and mesenchymal development processes [18]. Several studies reported that SOX12 is up-regulated and contribute to initiation and progression of several cancers, including gastric cancer [19], colorectal cancer [20], hepatocellular carcinoma [21] and lung cancer [22]. Recently a study showed that SOX12 expression was up-regulated in breast cancer tissues, and knockdown of SOX12 inhibited breast cancer proliferation, migration and invasion in vitro, and suppressed tumor growth in vivo [23], suggesting that SOX12 play an oncogenic role in breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Sex determining region Y-box protein (SOX) 12 (SOX12), an important member of the SOX family, was reported to play crucial roles in cardiac, neuronal and mesenchymal development processes [18]. Several studies reported that SOX12 is up-regulated and contribute to initiation and progression of several cancers, including gastric cancer [19], colorectal cancer [20], hepatocellular carcinoma [21] and lung cancer [22]. Recently a study showed that SOX12 expression was up-regulated in breast cancer tissues, and knockdown of SOX12 inhibited breast cancer proliferation, migration and invasion in vitro, and suppressed tumor growth in vivo [23], suggesting that SOX12 play an oncogenic role in breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Du et al (29) demonstrated that SOX12 may represent a novel prognostic biomarker and regulator of gastric cancer metastasis via upregulating MMP7 and insulin-like growth factor 1. According to a previous study, SOX12 may serve as a prognostic biomarker of CRC, and promotes CRC cell proliferation and metastasis via regulating asparagine synthesis (30). In the present study, western blot analysis demonstrated that NRSN2-knockdown decreased SOX12 expression, while NRSN2 overexpression upregulated SOX12 expression, indicating that NRSN2 may exert accelerative effects on CRC progression by recruiting SOX12.…”
Section: Discussionsupporting
confidence: 67%
“…Consistent with the observations in the patients, downregulation or overexpression of the three enzymes had opposite effects on cell proliferation and metastasis development. The role of Asn in these effects was confirmed by the inhibition of tumor growth and metastasis by ASNase (71).…”
Section: Asns In Cancer: Beyond Asn Synthesis?mentioning
confidence: 84%
“…Looking for regulators of the metastatic behavior in human colon cancer, Duquet et al (70) identified the sex-determining region Y (SRY)-box, member 12 (SOX12), as a suppressor of metastatic behavior of HT29 xenografts. However, in a more recent paper, Du et al (71) demonstrate that in two independent, large colorectal cancer cohorts HIF-1α-mediated SOX12 overexpression is not only associated with a metastatic behavior, but also with a poor prognosis. Moreover, it also enhanced cell proliferation in vitro.…”
Section: Asns In Cancer: Beyond Asn Synthesis?mentioning
confidence: 98%